To Ask or Not to Ask! That is the Question!: Scaffolding Thinking through Questioning - Fazhuda Abd. Aziz (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Education in general is a very dynamic field. It is constantly changing, developing, and evolving to suit, match and fulfill the demand of current trends. The current trend in education today is the 21st century skills; critical thinking, communication, collaboration and creativity, the teachers need to equip the students with. As teacher, our goal is to provide an opportunity for students to make the transition from learning to thinking to creating. Questions as a form of thinking tool to provoke students thinking and their schemata stimulate their curiosity, attract their attention and providing a more structured way of making that transition from learning to thinking to creating. Asking question can be beneficial in scaffolding learning especially in ELT. Questioning has always been regarded as an effective tool to enhance and stimulate students learning. It acts as a stimulus to promote thinking, enquiry and in depth processing of concepts as well as promotes classroom interaction between teachers and students. There is certainly an art to questioning effectively and learning to ask question is essential for both teachers and students. Thus questioning plays an essential role in creating an environment conducive to learning. This paper will look at how teachers can use questioning tools like taxonomies (Blooms Revised Bloom COGAFF and Revised COGAFF) to guide and assist them in formulating effective question in meaningful ways in order to scaffold students thinking.